The adequacy of Public Bus Fleet during the Covid-19 Pandemic (Case of The Transjakarta Corridor 1 DKI Jakarta, Indonesia) - Amanda Dian W. Kusumawardani; Ibnu Syabri; Fika Novitasari; Naya C. Drestalita (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Indonesia entered the “New Normal” era from the Covid-19 pandemic conditions in June 2020. Transjakarta is one of the public transportation used by the people of DKI Jakarta. With the beginning of the “New Normal” condition, people will start using public transportation such as Transjakarta. The quality of service that is reflected in the adequacy level of Transjakarta modes can endanger the health of the users of the modes. This study emphasized to identify the adequacy of the public bus fleet during the Covid-19 Pandemic. The location chosen in this study is the Transjakarta Corridor 1 (Blok M - Kota) bus, DKI Jakarta Province, Indonesia. This supply-demand analysis was conducted to determine the needs of Transjakarta Corridor 1 (Blok M - Kota) buses based on several calculation scenarios. Based on the results of the analysis, when the scenario has a maximum transport capacity of 75%, the articulated bus fleet has been able to meet its needs, while the single / maxi bus has not been able to meet the needs. The results obtained suggest both government and PT Transjakarta need to address passengers' perceptions of safety, through increasing the number of bus fleets, frequency of services, and bus headway.